Influence of surfactant types on correlation of retention factor and hydrophobicity of selected triazole fungicides in micellar electrokinetic chromatography - Wan Ibrahim, Wan Aini; Hermawan, Dadan; Hasan, Mohamed Noor; Sanagi, Mohd. Marsin (Malaysian Society of Analytical Sciences, 2008)
Application of micellar electrokinetic chromatography (MEKC) in quantitative structure-retention relationship (QSRR) has been studied for selected triazole fungicides. Effect of different surfactant types and concentrations of bile salts and sodium dodecyl sulfate on the correlation between logarithm of retention factor (log k) in MEKC and logarithm of octanol-water partition coefficient (log Pow) was investigated. Five standard fungicides (cyproconazole, bromuconazole, epoxiconazole, bitertanol and difenoconazole) with known log Pow values from 2.9 to 4.3 were used for constructing the calibration curve of log Pow against the MEKC retention factor, log k. High correlations were observed between hydrophobicity (log Pow) and log k in MEKC using two bile salt surfactants viz. sodium cholate and sodium deoxycholate and mixed bile salt systems, with squared correlation coefficient of linear regression greater than 0.98, due to the similar hydrogen bonding interaction patterns between bile salts MEKC systems and the octanol-water system.